Sile (Pencak Silat Nias) as a Negotiation of Religion and Culture between Traditional Societies, Islam, and Christianity in Ono Niha - Waruwu, Famati; Tambunan, Elia; Harefa, Otieli; Gulo, Nestilina; Apvan Bertin Baene, Ria (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Pencak Silat is no longer limited to martial arts but goes far beyond this. Suppose it is generally understood as a martial art commonly called Sile. In that case, it needs to be seen from the socio-theological praxis of the people of Moro’ö District, West Nias Regency, and the people of Tugala Oyo District, North Nias Regency, where they are Nias people in general who tend to believe traditionally based on customs, as well as Christian church congregations, including Muslims. This article delves into Nias’ traditional pencak silat in 2022-2023. The empirical problem in Christianity is that there is a tendency to label synchronicity that pencak silat as a traditional rite for primitive people, has always been associated with an attempt to display the dimension of “evil spirits” as opposed to the “good spirits” in the Christian faith with the modern eyes of urban people. Meanwhile, Muslims tend to be positioned as immigrants. This paper is in the social setting of North and West Nias as a research field, and it is carried out with empirical qualitative research with a socio-theological approach. Data were collected by observation, interview, and documentation. It was found that there is an increasing immersion in cultural arts expressed through pencak silat as a social space (medium) for people of different faiths and traditions. It was found that North and West Nias Sile displayed spatial negotiations between culture and religion.